Education and innovation in the utilization of Beronok (Meranti Sea Cucumber) for sustainable development and community well-being in Meranti - Rahmad Hari Adi; Barlian Eri; Welis Wilda (BIO Web of Conferences)
The Meranti Regency is endowed with a rich biodiversity, including the sea cucumber, locally known as beronok, which the local community has recognized for its high nutritional value. This article explores how education and innovation in the utilization of beronok contribute to sustainable development for community well-being. With its high content of protein, minerals, and other health benefits, beronok holds significant potential as a functional food source that can support nutrition and foster sustainable livelihoods. Educational programs and innovative approaches encourage the community to utilize beronok more efficiently, improving food security, promoting healthier lifestyles, and supporting sustainable living practices. These initiatives not only aim to enhance the local population’s nutrition but also provide socio-economic opportunities through the responsible use of natural resources, fostering long-term sustainability. By building the community’s capacity to process and manage beronok sustainably, this approach promotes resilience and well-being. The study emphasizes the integration of local resources, education, and innovation into sustainable development strategies, ensuring a balance between ecological conservation, community empowerment, and improved living standards. This holistic approach ensures that the Meranti community achieves sustainable development for life and well-being, benefiting both present and future generations.